Институциональные аспекты стратегии и капитализации предприятий - Булеев, И.П.; Брюховецкая, Н.Е. (Економічний вісник Донбасу, 2010)
Розглянуті інституційні аспекти стратегії підприємства. Досліджена суть, структура капіталізації, обґрунтована класифікація капіталізації. Доведена необхідність включення капіталізації в стратегію підприємства. Визначені джерела й шляхи підвищення капіталізації підприємства. Ключові слова: стратегія, капіталізація, інститути, підприємства, розвиток. Рассмотрены институциональные аспекты стратегии предприятия. Исследована сущность, структура капитализации, обоснована классификация капитализации. Доказана необходимость включения капитализации в стратегию предприятия. Определены источники и пути повышения капитализации предприятия. Ключевые слова: стратегия, капитализация, институты, предприятия, развитие. The institutional aspects of strategy of enterprise are considered. Essence, structure of capitalization, is investigational, classification of capitalization is grounded. The necessity of including of capitalization in strategy of enterprise is well-proven. Sources and ways of increase of capitalization of enterprise are certain. Keywords: strategy, capitalization, institutes, enterprises, development.